Challenges of anti-smoking campaign in Malaysia from the healthcare provider perspective - Mohamad Helmy J; Normalina A; Afzan MY; Muhammad Lokman MI (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
This study discovered challenging of the anti-smoking campaign from the perspective of healthcare providers in Kuantan. The objectives of this study were to explore the challenges of the anti-smoking campaign from healthcare providers’ views, to explore the awareness regarding the existence of Smoking Cessation Clinics and to explore the ways to improve anti-smoking campaigns. This study is important because it may aid Malaysian authorities to develop better strategies in promoting anti-smoking campaigns in the future. Purposive sampling was used in the collection of data and semi-structured interviews were conducted among five healthcare providers from three selected Smoking Cessation Clinics. This study found that healthcare provider felt that smokers who received treatment from the Health Centre had low understanding of the standard of procedure of smoking cessation procedure, low commitment and easily influenced by the public. Healthcare provider also felt that multidisciplinary task limited their focus to the client. Besides, they felt that the existence of smoking Cessation Clinic needs to be widely publicised to the community. Through the findings, the author recommend to improve the current approaches to reduce the number of smokers in Malaysia such as improving publicity to the public, enhancing the law of enforcement and providing incentives.